2020
DOI: 10.3389/fphy.2020.00138
|View full text |Cite
|
Sign up to set email alerts
|

4DFlowNet: Super-Resolution 4D Flow MRI Using Deep Learning and Computational Fluid Dynamics

Abstract: 4D flow magnetic resonance imaging (MRI) is an emerging imaging technique where spatiotemporal 3D blood velocity can be captured with full volumetric coverage in a single non-invasive examination. This enables qualitative and quantitative analysis of hemodynamic flow parameters of the heart and great vessels. An increase in the image resolution would provide more accuracy and allow better assessment of the blood flow, especially for patients with abnormal flows. However, this must be balanced with increasing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 25 publications
0
74
0
1
Order By: Relevance
“…The proposed DL framework required complicated methodology to generate training data. A simulated training data approach (ie, CFD generated flow profiles) as used by Ferdian et al 22 may serve as a simpler alternative for generating DL training data. Despite our best efforts, a large portion of the total reconstruction time for CS and DL was due to pre‐processing time [DL = 40.9 s (88.0% of total recon time), CS = 62.6 s (30.0 % of total recon time)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed DL framework required complicated methodology to generate training data. A simulated training data approach (ie, CFD generated flow profiles) as used by Ferdian et al 22 may serve as a simpler alternative for generating DL training data. Despite our best efforts, a large portion of the total reconstruction time for CS and DL was due to pre‐processing time [DL = 40.9 s (88.0% of total recon time), CS = 62.6 s (30.0 % of total recon time)].…”
Section: Discussionmentioning
confidence: 99%
“…Vishnevskiy et al 21 showed that an unrolled network incorporating a physics‐based model into the DL architecture reduces reconstruction time 30‐fold compared to CS for 12.4‐ to 13.8‐fold accelerated 4D ECG‐gated segmented PC MRI with 25 cardiac phases. Ferdian et al 22 showed that 4DFlowNet network trained using synthetic 4D flow MR generated from computational fluid dynamic (CFD) solutions could be used to increase spatial resolution. Nath et al 23 showed that a U‐net could filter aliasing artifact from accelerated (2.5‐fold ≤ acceleration rate ≤ 5‐fold) 2D PC MRI, while outperforming CS.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, reliable imaging of the LAA flow field is extremely challenging, especially in the proximity of the vessel wall, making it nearly impossible to obtain accurate values of derived hemodynamic indices such as the wall shear stress or the ECAP (Petersson et al, 2012 ). In this regard, attempts have already been made to tackle said limitations such as the development of Dual-V enc acquisition sequences (Callahan et al, 2019 ) or leveraging CFD simulations to obtain 4D flow super-resolution (Ferdian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the family of Kalman filter data assimilation models provides the means to improve the accuracy of computational models by leveraging even imperfect experimental data. There are a growing number of studies in the literature on merging CFD and 4D flow MRI data using data assimilation [70,[77][78][79][80][81]. PIV is another popular approach in haemodynamics quantification.…”
Section: Opportunities and Challengesmentioning
confidence: 99%